Siglec-7 Mediates Immunomodulation by Colorectal Cancer-Associated Fusobacterium nucleatum ssp. animalis - Lamprinaki, Dimitra; Garcia-Vello, Pilar; Marchetti, Roberta; Hellmich, Charlotte; McCord, Kelli A.; Bowles, Kristian M.; Macauley, Matthew S.; Silipo, Alba; De Castro, Cristina; Crocker, Paul R.; Juge, Nathalie (Frontiers in Immunology, 2021)
Fusobacterium nucleatum is involved in the development of colorectal cancer (CRC) through innate immune cell modulation. However, the receptors of the interaction between F. nucleatum ssp. and immune cells remain largely undetermined. Here, we showed that F. nucleatum ssp. animalis interacts with Siglecs (sialic acid–binding immunoglobulin-like lectins) expressed on innate immune cells with highest binding to Siglec-7. Binding to Siglec-7 was also observed using F. nucleatum-derived outer membrane vesicles (OMVs) and lipopolysaccharide (LPS). F. nucleatum and its derived OMVs or LPS induced a pro-inflammatory profile in human monocyte-derived dendritic cells (moDCs) and a tumour associated profile in human monocyte-derived macrophages (moMs). Siglec-7 silencing in moDCs or CRISPR-cas9 Siglec-7-depletion of U-937 macrophage cells altered F. nucleatum induced cytokine but not marker expression. The molecular interaction between Siglec-7 and the LPS O-antigen purified from F. nucleatum ssp. animalis was further characterised by saturation transfer difference (STD) NMR spectroscopy, revealing novel ligands for Siglec-7. Together, these data support a new role for Siglec-7 in mediating immune modulation by F. nucleatum strains and their OMVs through recognition of LPS on the bacterial cell surface. This opens a new dimension in our understanding of how F. nucleatum promotes CRC progression through the generation of a pro-inflammatory environment and provides a molecular lead for the development of novel cancer therapeutic approaches targeting F. nucleatum-Siglec-7 interaction.